2019
DOI: 10.21203/rs.2.11186/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A meta-analysis of comparison of proximal gastrectomy with double-tract reconstruction and total gastrectomy for proximal early gastric cancer

Abstract: Background In theory, proximal gastrectomy with double-tract reconstruction (PG-DT) was superior to total gastrectomy (TG) in hematologic and nutritional outcomes. However, its clinical effects in proximal early gastric cancer (EGC) have been controversial. Methods The purpose of this study was to investigate the outcomes of laparoscopic proximal gastrectomy with double-tract reconstruction (LPG-DT) for proximal EGC. For this systematic review and meta-analysis, we searched for articles published before Decemb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…We did not investigate PG with EJ stomy because a number of studies showed that PG with EG stomy was associated with a higher incidence of complications such as reflux, stenosis, and stricture than TG [ 15 , 23 , 39 ]. Furthermore, several studies reported that there was no significant difference in surgical outcomes between LPG with DTR and LTG [ 3 , 24 , 25 , 27 , 40 42 ]. In a previous study, LPG with DTR did not increase the incidences of reflux esophagitis and anastomotic stenosis compared to LTG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not investigate PG with EJ stomy because a number of studies showed that PG with EG stomy was associated with a higher incidence of complications such as reflux, stenosis, and stricture than TG [ 15 , 23 , 39 ]. Furthermore, several studies reported that there was no significant difference in surgical outcomes between LPG with DTR and LTG [ 3 , 24 , 25 , 27 , 40 42 ]. In a previous study, LPG with DTR did not increase the incidences of reflux esophagitis and anastomotic stenosis compared to LTG.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the incidence of reflux symptoms, usage of proton pump inhibitors, and anastomotic strictures were significantly lower in the DTR than in the EG stomy group [23]. Li et al performed a meta-analysis to compare the use of LPG-DTR and TG for proximal early gastric cancer [25]. They concluded that PG-DTR is comparable to TG for patients with proximal early gastric cancer, and reported that LPG-DT not only appears superior to TG in terms of preventing vitamin B 12 deficiency, but also does not increase the risks of anastomotic stricture and reflux esophagitis.…”
Section: Introductionmentioning
confidence: 99%
“…The esophagojejunostomy techniques, such as that done with jejunal interposition (JI) or DTR, are now thought to be alternatives to esophagogastrostomy (EG) reconstruction after PG to prevent postoperative complications [7, 51, 52]. For example, Li et al [53] showed that there was no difference statistically in anastomotic stenosis and reflux esophagitis between laparoscopy-assisted proximal gastrectomy (LAPG) with DTR and laparoscopy-assisted total gastrectomy (LATG), which showed an optimistic prospect for PG feasibly.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the risk of leakage is increased. However, a latest meta-analysis consisted of 592 patients found that laparoscopic proximal gastrectomy with double-tract reconstruction (PG-DTR) had comparable short-term outcome with laparoscopic total gastrectomy (TG) [26]. As a novel reconstruction procedure considered superior to TG in term of nutrition, the clinical outcomes of PG-DTR were still controversial.…”
Section: Discussionmentioning
confidence: 99%